Identification and Classification of Constraints and Problems of Warehousing System: A Case Study of Telangana Stakeholders - Kadakanchi Divya; D. A. Rajini Devi; K. Suhasini; A. Meena (Archives of Current Research International, 2024)
Aims: To identify the problems and constraints of stakeholders in warehousing system in Telangana state. Place and Duration of Study: The study was conducted in Mahbubnagar and Jagtial districts of Telangana state, which were selected purposively based on the number of warehouses available in the districts. The study was conducted between 2023 to 2024. Methodology: The sample consists of 120 respondents which include different stakeholders viz., farmers, warehouse investors, warehouse managers, Handling and Transportation (H&T) contractor, H&T labour, Junior Assistant and Technical Assistant. All the stakeholders were selected using random sampling technique. Garrett’s ranking technique was employed to analyze the data.The data was collected through personal interview method using pre-tested schedules. Results: The study revealed that, the absence of warehouse space was regarded as the major constraint experienced by farmers, with a mean score value of 71.77, followed by financial difficulties in paying off debts (55.7). Two biggest challenges experienced by warehouse investors were limited stock arrivals (69.375) and stock rejections due to poor quality (62.5). The primary challenge, according to the warehouse manager and H&T contractor, is the shortage of labour for stocking, loading, and unloading of lots. H&T labour reported the major constraints they faced was lack of frequent employment (62.38) followed by migration from native places in search of work (57.88). Technical assistants have identified two constraints and they are changes in standard operating procedures (65.625) and extended working hours during peak seasons (60.625). Junior assistants had faced difficulties with maintaining pest-free goods (63.125) and rodent-caused storage losses (51.25). Conclusion: The study recommends providing more storage facilities and issuing Nego able Warehouse Receipts to farmers, as well as improving the living conditions of H&T labourers to ensure their stable employment. Additionally, regular pest control and adherence to standardized warehouse management procedures are crucial for system improvement